Impact of a College Course on the Sustainability of Student Diets in Terms of the Planetary Boundaries for Climate Change and Land, Water, Nitrogen and Phosphorus Use - Whitener, Victoria A.; Cook, Brian; Spielbauer, Ingrid; Nguyen, Paula Karyn; Jay, Jennifer A. (Frontiers in Sustainable Food Systems, 2021)
While it is widely acknowledged that shifts in diet could play a large role in mitigating climate change with important health co-benefits, knowledge on how to accomplish these shifts is lacking. Our previous study showed a statistically significant reduction in the dietary carbon footprint of students who had completed a college course on the connections between food and the environment compared to a control group enrolled in an unrelated course. An extension of the previous study, this research evaluates the sustainability of female and male diets in both the intervention and control groups from baseline to follow up with respect to the following planetary boundaries: greenhouse gases, land use, water use, nitrogen loss, and phosphorus use. In addition, a 50-point modified Alternative Healthy Eating Index was calculated at baseline and follow up for all students. Female students enrolled in the intervention course reported diets with statistically significant reductions in their footprints from baseline to follow up for greenhouse gases (p = 0.011), land use (p = 0.012), and phosphorus (p = 0.045), and the female diets were statistically different from the control groups for those three boundaries. For water use, female diets increased in footprint from baseline to follow up due to an increase in vegetable intake. Males enrolled in the intervention showed similar trends (reductions in footprints for greenhouse gases, land use, and phosphorus use and an increase in blue water use), but differences were not statistically significant, partially due to the smaller number of male respondents. Student dietary footprints are compared to a per capita limit allowable for food according to the planetary boundaries concept. For all of the planetary boundaries except blue water use, the student dietary footprints were well above the per capita boundary for food-related sources.